PONDOK PESANTREN DARUL QURAN BANDUNG DALAM SISTEM PENDIDIKAN NASIONAL - Heti Aisah; Ahmad Jaelani; Nurwadjah Ahmad E.Q.; Andewi Suhartini (Tarbiyatuna Kajian Pendidikan Islam, 2021)
Pesantren is an Islamic religious education institution that has Kiai, santri, huts and mosques. Islamic boarding schools have made a major contribution in their role in advancing the world of education in Indonesia. This article aims to examine the role of the Darul Quran Islamic boarding school in implementing the national education system. The research uses descriptive qualitative research methods, with data collection techniques through interviews, documentation studies and observations. The results showed that the Darul Quran Islamic boarding school in Bandung City was able to show its role in the National education system, through the Darul Quran method, and the Daili Activity which led its students to have attitudes, knowledge and skills in fulfilling 21st century competencies.